2019
DOI: 10.1177/2150135119859879
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Neurally Adjusted Ventilatory Assist Versus High Flow Cannula Support After Congenital Heart Surgery

Abstract: Background: Extubation failure rates for critical patients in pediatric intensive care units (ICUs) range from 5% to 29%. Noninvasive (NIV) ventilation has been shown to decrease extubation failure. We compared reintubation rates and outcomes of patients supported with NIV neurally adjusted ventilation assist (NAVA) versus historical controls supported with high-flow nasal cannula (HFNC). Methods: Case–control study of infants less than three months of age who underwent cardiac surgery and received NIV support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Different from our results, some studies (33,34) have suggested the postoperative use of HFNC can reduce reintubation, but there is a lack of relevant studies for obese or cardiac surgery patients. Compared with COT, the use of HFNC can shorten the length of stay in the ICU (35,36). Our results showed that this is not consistent among obese patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Different from our results, some studies (33,34) have suggested the postoperative use of HFNC can reduce reintubation, but there is a lack of relevant studies for obese or cardiac surgery patients. Compared with COT, the use of HFNC can shorten the length of stay in the ICU (35,36). Our results showed that this is not consistent among obese patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 55%
“…Two studies reported the dyspnea score at 24 h postoperative and in vivo 35 7). Using a random-effects model, the result was not found to be statistically significant (p=0.69).…”
Section: Dyspnea Score At 24 H Postoperative (Improvement)mentioning
confidence: 99%
“…In a cohort study focused on ventilation in premature neonates after weaning, NIV-NAVA and NIPPV exhibited the same ventilatory efficiency 19 . In a case-control study NIV-NAVA was selected as weaning mode for ventilatory support of term infants after congenital heart surgery which did not contribute to extubated success, compared with selecting HFNC 34 . Consequently, whether NIV-NAVA is superior to conventional NIV remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…119 Noninvasive NAVA after extubation has not shown to be specifically helpful. 120 Invasive support requires placement of an endotracheal tube. Because their patients often require invasive support for extended periods, neonatologists prefer uncuffed tubes, 29 tolerating and compensating for leaks around the tube in the interest of minimizing pressure injury to the tracheal mucosa and risk for subsequent subglottic or tracheal stenosis.…”
Section: Ventilator-induced Lung Injurymentioning
confidence: 99%